Dyslipidemia and serum cystatin C levels as biomarker of diabetic nephropathy in patients with type 2 diabetes mellitus - Dejenie, Tadesse Asmamaw; Abebe, Endeshaw Chekol; Mengstie, Misganaw Asmamaw; Seid, Mohammed Abdu; Gebeyehu, Natnael Atnafu; Adella, Getachew Asmare; Kassie, Gizchew Ambaw; Gebrekidan, Amanuel Yosef; Gesese, Molalegn Mesele; Tegegne, Kirubel Dagnaw; Anley, Denekew Tenaw; Feleke, Sefineh Fenta; et al. (Frontiers in Endocrinology, 2023)
Background: Diabetic nephropathy is a leading cause of end-stage renal disease. The diagnostic markers of nephropathy, including the presence of albuminuria and/or a reduced estimated glomerular filtration rate, are not clinically ideal, and most of them are raised after a significant reduction in renal function. Therefore, it is crucial to seek more sensitive and non-invasive biomarkers for the diagnosis of diabetic nephropathy. Objective of the Study: This study aimed to investigate the serum cystatin C levels and dyslipidemia for the detection of diabetic nephropathy in patients with type 2 diabetes mellitus. Methodology: A hospital-based cross-sectional study was conducted from December 2021 to August 2022 in Tikur, Anbessa specialized teaching hospital with a sample size of 140 patients with type2 diabetes mellitus. Socio-demographic data was collected using a structured questionnaire, and 5 mL of blood was collected from each participant following overnight fasting for biochemical analyses. Results: In type 2 diabetes patients with nephropathy, we found significant lipoprotein abnormalities and an increase in serum cystatin C (P < 0.001) compared to those without nephropathy. Serum cystatin C, systolic blood pressure, fasting blood glucose, total cholesterol, triglyceride, low density lipoprotein, very low density lipoprotein, high density lipoprotein, and duration of diabetes were identified as being significantly associated with diabetic nephropathy (P < 0.05) in multivariable logistic regression analysis. The mean values of total cholesterol levels, triglyceride levels, and high-density lipoprotein cholesterol levels were also found to be significantly higher (P < 0.05) in females as compared to male type-2 diabetic patients. The fasting blood glucose levels and lipid profiles of the participants were found to be significantly associated with serum cystatin C levels. Conclusion: The study concluded that cystatin C levels in serum are a useful marker for the evaluation of renal disease in diabetes patients. It also found significant lipoproteins abnormalities in type 2 diabetes patients with diabetic nephropathy when compared with those without diabetic nephropathy.